Corn Stover Harvest, Tillage, and Cover Crop Effects on Soil Health Indicators. Issue 4 (2nd August 2018) - Obrycki, John F.; Karlen, Douglas L.; Cambardella, Cynthia A.; Kovar, John L.; Birrell, Stuart J.
Abstract : Core Ideas: In no‐till continuous corn, cover crops increased potentially mineralizable N. Particulate organic matter C responded to tillage and residue removal at 0 to 5 cm. Stover removal for 5 yr negatively affected 2 of 12 measured soil properties. Monitoring soil health indicators (SHI) will help ensure that corn ( Zea mays L.) stover harvest is sustainable. This study examines SHI changes after 5 yr of growing continuous corn with either chisel plow or no‐tillage practices and harvesting 0, ∼35, or ∼60% of the stover. Two no‐tillage treatments with a cereal rye ( Secale cereale L.) cover crop and stover harvest rates of ∼35 or ∼60% were evaluated. All eight treatments were replicated four times in a randomized complete block design at an 11‐ha site in Boone County, IA. Soil samples were collected following grain and stover harvest from 0‐ to 5‐ and 5‐ to 15‐cm depth increments. Particulate organic matter C (POM‐C) decreased when stover was removed or the soil was chisel plowed. No‐till with 0% stover removal had 10 mg g –1 POM‐C in the 0‐ to 5‐cm soil layer, which was 1.9‐fold higher than in other treatments. Potentially mineralizable N (PMN) was greater under cover crop treatments. Average PMN values were 56.9 and 45.5 µg g –1 PMN for no‐till with cereal rye at 0‐ to 5‐ and 5‐ to 15‐cm depths, respectively, compared with 17.5 and ‐3.7 µg g –1 PMN for the same no‐till treatments without cereal rye. Other soil properties did not respond to increasing levels of stover removal. At this location and at the studied removal rates, 5 yr of harvesting corn stover did not decrease soil health, but POM‐C data suggest that changes may be occurring. Long‐term monitoring should continue to assess corn stover harvest sustainability.